Respons Terapi pada Penderita Karsinoma Nasofaring di Jawa Barat - Randika Rachman; Ifiq Budiyan Nazar; Nur Akbar Aroeman; Yussy Afriani Dewi (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Nasopharyngeal carcinoma (NPC) is one of the most common head and neck malignancies in Southeast Asia, including Indonesia, particularly in West Java. The disease is frequently diagnosed at an advanced stage, which affects therapeutic outcomes. This study aimed to describe the treatment response of NPC patients in West Java and identify clinical patterns associated with therapeutic outcomes. This cross-sectional study involved NPC patients who underwent therapy at Hasan Sadikin Hospital, Santosa Kopo Hospital, and Al-Ihsan Hospital, Bandung, from 2016 to 2020. Data were collected from medical records with histopathological confirmation, including age, sex, stage, and therapeutic response, which was categorized as complete, partial, stable, or progressive. Among 985 new NPC cases, most patients were male (70.5%), with WHO type 3 (92.2%) and stage IVA (35.4%) being the most common findings. The predominant therapeutic response was partial (45.6%), followed by complete (33.5%), stable (17.8%), and progressive (3.1%). The majority of NPC patients in West Java showed a partial therapeutic response, primarily among those treated at advanced stages. Early detection and timely therapy are essential to improve treatment effectiveness and patient prognosis. Keywords: Indonesia, Nasopharyngeal Carcinoma, Stage, Therapeutic Response, West Java.  ABSTRAK Karsinoma nasofaring (KNF) merupakan salah satu jenis keganasan kepala-leher dengan insidensi tinggi di Asia Tenggara, termasuk Indonesia, khususnya di Jawa Barat. Penyakit ini sering terdiagnosis pada stadium lanjut, yang berdampak pada efektivitas terapi. Penelitian ini bertujuan untuk menggambarkan respons terapi pasien KNF di Jawa Barat dan mengidentifikasi pola klinis yang berhubungan dengan hasil pengobatan. Penelitian potong lintang ini melibatkan pasien KNF yang menjalani terapi di RS Hasan Sadikin, RS Santosa Kopo, dan RS Al-Ihsan Bandung pada periode 2016–2020. Data dikumpulkan dari rekam medis pasien dengan diagnosis histopatologis KNF, mencakup usia, jenis kelamin, stadium, dan hasil terapi. Respons terapi diklasifikasikan menjadi komplit, parsial, stabil, dan progresif. Dari 985 kasus KNF, mayoritas pasien berjenis kelamin laki-laki (70,5%), dengan WHO tipe 3 (92,2%) dan stadium IVA (35,4%) sebagai temuan terbanyak. Respons terapi terbanyak adalah parsial (45,6%), diikuti oleh komplit (33,5%), stabil (17,8%), dan progresif (3,1%). Respons terapi pasien KNF di Jawa Barat terbanyak adalah parsial, terutama pada pasien dengan stadium lanjut. Deteksi dini dan terapi pada tahap awal sangat diperlukan untuk meningkatkan keberhasilan pengobatan dan prognosis pasien. Kata Kunci: Indonesia, Jawa Barat, Karsinoma Nasofaring, Respons Terapi, Stadium.